Pengaruh Iklan E-Commerce Shopee di Youtube terhadap Perilaku Konsumtif Mahasiswa - Risky Dwian E; Resti Mutiara W; Septi Wulan Dari; Vicky F Sanjaya (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
The aim of this research is to determine the effect of Shopee e-commerce advertising on YouTube on student consumer behavior (case study of students at the Islamic Economics and Business Faculty of UIN Raden Intan Lampung). This research uses a quantitative approach. The data used is primary data by distributing questionnaires online via Google from. The population in this study were students from the Faculty of Islamic Economics and Business at UIN Raden Intan Lampung who had shopped at Shopee. The sample used was 92 respondents and was taken by purposive sampling, namely a technique for determining samples with certain considerations. With the help of the SmartPLS Test tool 4. The research results show that the impact of exposure to Shopee advertising on YouTube has a positive and significant effect on consumer behavior. Because the results of the Reliability Test on the influence variable of advertising exposure (X) have a positive and significant effect greater than 0.6, namely Crombach's Alph 0.889 in the supporting direction (Y), namely the value of Crombach's Alph 0.943.